Synthesis, characterization and programmable toxicity of iron oxide nanoparticles conjugated with d-amino acid oxidase. Issue 3 (5th January 2017) - Balzaretti, Riccardo; Meder, Fabian; Monopoli, Marco P.; Boselli, Luca; Armenia, Ilaria; Pollegioni, Loredano; Bernardini, Giovanni; Gornati, Rosalba
Abstract : Rg DAAO conjugated to γ-Fe2 O3 NPs generates a low toxic NP-DAAO system, which kills cancer cells through ROS production. Abstract : d -amino acid oxidase (DAAO) is an enzyme which generates reactive oxygen species (ROS) and it is believed to have potential uses as a novel therapeutic molecule if internalized by cancer cells or if they are localized close to their plasma membrane. When conjugated onto iron oxide nanoparticles (NPs), the enzyme can be magnetically directed to targeted locations with an increased efficacy. A subsequent injection of DAAO substrated -alanine can initiate ROS production and induce apoptosis of cells surrounding the NP-DAAO complex. Here, we describe a platform for optimal bioconjugation using monodisperse γ-Fe2 O3 NPs (∼10 nm) resulting in high DAAO loading, stable NP-DAAO dispersions and more than 90% enzymatic activity recovery, which is retained using the particles in human serum. Lastly, since the NP-DAAO system is designed for cancer therapy, we proved its efficacy in killing SKOV-3, U87 and HCT-116 cancer cells.